(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The growing complexity of communication in modern educational and professional contexts requires language learners to develop not only communicative competence but also meta-competence. Meta-competence refers to learners’ ability to reflect on, monitor, regulate and adapt their language use according to different communicative situations. This article explores the integration of meta-competence into Communicative Language Teaching (CLT) and examines its potential to enhance learners’ communicative effectiveness. Drawing upon contemporary theories of language learning, metacognition and communicative competence, the paper argues that meta-competence serves as a crucial component in fostering learner autonomy, critical thinking and strategic communication skills.